Differentiating between feline pleural effusions of cardiac and non‐cardiac origin using pleural fluid NT‐proBNP concentrations. (7th November 2013) - Humm, K.; Hezzell, M.; Sargent, J.; Connolly, D. J.; Boswood, A.
<x xml:space="preserve">Abstract</x> Objective To assess whether pleural fluid and urine amino terminal proB‐type natriuretic peptide (NT‐proBNP) can distinguish cardiac from non‐cardiac causes of pleural effusion. Methods Blood, urine and pleural fluid were prospectively collected from cats presenting with pleural effusion categorised as cardiac or non‐cardiac in origin. NT‐ProBNP concentrations were measured using a feline‐specific enzyme‐linked immunosorbent assay. Groups were statistically compared and receiver operating characteristic curves constructed to determine cut‐offs to distinguish cardiac from non‐cardiac pleural effusion in plasma, pleural fluid and urine. Results Forty cats with pleural effusion (22 cardiac and 18 non‐cardiac) were studied. NT‐proBNP concentrations in plasma and pleural fluid were strongly correlated. Plasma (P<0·001) and pleural fluid (P<0·001) NT‐proBNP concentrations and urinary NT‐proBNT/creatinine ratios (P=0·035) were significantly higher in the cardiac group. After receiver operating characteristic curve analysis a plasma NT‐proBNP cut‐off of 214·3 pmol/mL was suggested [sensitivity=86·4% (95% CI: 66·7 to 95·3%), specificity=88·9% (95% CI: 67·2 to 96·9%)] and a pleural fluid NT‐proBNP cut‐off of 322·3 pmol/mL was suggested [sensitivity=100% (95% CI: 85·1 to 100%), specificity=94·4% (95% CI: 74·2 to 99·0%)]. No cut‐off with adequate sensitivity and specificity for urinary NT‐proBNP/creatinine ratios was suggested. Clinical Significance Measurement of NT‐proBNP in pleural fluid distinguishes cardiac from non‐cardiac causes of pleural effusion in cats.